Proceso de atención de enfermería en paciente de 20 años, con fractura de 1er, 2do y 3er metatarsiano. - Malca Ati, Wilmer Rene (2020)
Fractures and injuries of the extremities are very frequent produced in motorcycle traffic accidents; In the evaluation, we found a 20-year-old male patient at the moment, hemodynamically active, oriented in space and person time, who came to the emergency due to foot crush in a traffic accident with a clinical diagnosis of an exposed fracture in the right foot. after complementary examinations, emergency surgical intervention is performed since the trauma to the foot bones causes intense pain and edema in the affected areas, with surgical intervention in 1st, 2nd and 3rd metatarsal fractures; In the nursing care process we develop a care plan, related to moderate pain, since the time it takes for the fracture to heal could be from weeks to months, during the patient's stay we will help in tolerance to post-surgical stress, since a combination of metal cables, nails, screws and plates are used for its restoration and alignment of the bone, in the execution of the care the wound must be carefully observed because it can compromise other tissues such as the skin, nerves, blood vessels, and muscles and even necrosis and immobility; evaluate care results for a good recovery.